DÉTERMINANTS DE LA DÉMOBILISATION ET DE LA DÉMISSION DES MEMBRES DE L’UNION DES COOPÉRATIVES DE CACAO DE LA ZONE DE SASSANDRA (CÔTE D’IVOIRE) - Adja Ferdinand Vanga (European Scientific Journal, ESJ, 2012)
The pressure of the international financial institutions has necessarily brought about the reorganization of the sector of the binomial coffee-cocoa. The Ivorian State has set up a policy of deregulation of that sector with the transformation of Groupings dedicated to Cooperatives (GVC) into real cooperatives. However, following many cooperatives, the members of the union of the cooperatives of Sassandra are growing apathy and are prone to resignation.For data collection, investigations of a qualitative nature were carried out. They involved interviews with the persons in charge of the cooperatives that form the union and the members of the cooperative.It emerges from the investigations that services offered by the union of cocoa cooperatives in the area of Sassandra are not sufficient enough and effective to meet its members' socio-economic needs. Moreover, many irregularities were noted at the level of social communication, operation, organization, as well as financial management of the cooperative which contributed to the increase in the union‟s members‟ apathy and resignation.One of the immediate consequences of this situation is the fall in the union„s receipts in connection with the yield of the union of cooperatives in terms of quantity of cocoa produced.